The Influence of Two Cylinder Diesel Engine Modification (IDI to DI) on Its Performance and Emission - Yanuandri Putrasari; Arifin Nur; Aam Muharam (National Research and Innovation Agency, 2013)
Modification of combustion system from indirect injection (IDI) to direct injection (DI) was carried out on the two cylinder diesel engine, followed with tests for performance and emission. The modification from IDI to DI was conducted on a two cylinder diesel engine by removing the pre-chamber from the inside of the cylinder head, replacing the injector and its position to the top of the combustion chamber directly and also replacing the original piston with a piston that has a bowl on the crown. Performance and emission tests were conducted on 1,500 rpm with loads that vary from 0, 10, 20, 30, 40, 50, to 60 Nm. The investigation results of the diesel engine modification from IDI to DI showed several interesting phenomena. Further research is needed in order to increase the engine performance and reduce its emission.